Deterioration and maintenance of pavements - Pearson, Derek (ICE, 2012)
Originally developed as a set of course notes for an MSc module of the same name, this book is intended for new pavement engineers and focuses on the evaluation and repair of pavements. The author employs an easy-to-follow, colloquial style, while drawing extensively on his years of personal experience. The text is highly accessible and full of examples and case studies providing hands-on, practical guidance relating to a wide range of pavement-types.